Knowledge Management in E-Learning A Critical Analysis (International Journal of Engineering and Computer Science, 2017)
The integration of knowledge management (KM) and e-learning (EL) become inevitable day by day. KM applications focus in providing institutions with tools to enrich knowledge, while the EL focuses on managing the delivery of academic knowledge. But integration of both the areas is far more behind in research. This research proposed a KM model to provide 24x7 hours synchronous collaborative learning. Requirement of KM in EL is the focus of this paper by creating a new approach of KM and emphasizing on various processes accompanying. Several Artificial Intelligence (AI) tools and technologies such as big data, linked data, semantic web, 3D visualization, etc. are incorporated hypothetically to achieve the collaborative learning environment.